Pelaksanaan Penilaian Afektif dalam Evaluasi Pembelajaran terhadap Pembelajaran Pendidikan Agama Islam di SD Adabiah Padang: Penelitian - Dikriati Kamalasari; Remiswal; Khadijah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to see the implementation of affective assessment in the evaluation of learning of Islamic religious education learning at SD adabiah Padang. Affective assessment in effective learning evaluation is considered a cursory to improve the quality of assessment in overall learning. This study was conducted to see the role of affective assessment and its relationship with PAI learning which leads to learning evaluation. The research method used is qualitative which includes observation, interviews and documentation of the course of the affective assessment. By using the Literature study approach. The conclusion of the study shows that affective assessment is indeed the focus of attention in concluding the final assessment later and concluding that the existing assessment is not only focused on cognitive assessment.